2020
DOI: 10.1002/wnan.1639
|View full text |Cite
|
Sign up to set email alerts
|

Hot spot 19F magnetic resonance imaging of inflammation

Abstract: Among the preclinical molecular imaging approaches, lately fluorine (19 F) magnetic resonance imaging (MRI) has garnered significant scientific interest in the biomedical research community, due to the unique properties of fluorinated materials and the 19 F nucleus. Fluorine is an intrinsically sensitive nucleus for MRI-there is negligible endogenous 19 F in the body and, thus, no background signal which allows the detection of fluorinated materials as "hot spots" by combined 1 H/ 19 F MRI and renders fluorine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 117 publications
0
23
0
Order By: Relevance
“…Based on light irradiation from the ultraviolet, visible, and near-infrared spectrums, optical imaging techniques have high detection sensitivity but are limited by quenching and the photo-bleaching effect. Magnetic resonant imaging (MRI) is a radiation-free and non-invasive technique based on magnetic contrast agents such as Gadolinium (III), superparamagnetic iron oxide nanoparticles (SPIO), or perfluorocarbons (PFCs), and is characterized by high spatial resolution but with very low sensitivity 185 , 186 , 187 , 188 . Ionizing radiation such as positron emission tomography (PET) and single-photon emission computed tomography (SPECT) are based on the use of high-energy elements (radioisotopes) characterized by high-detection sensitivity (from nanomolar to picomolar) but with low spatial resolution 189 , 190 .…”
Section: Macrophage As Theranostic Toolsmentioning
confidence: 99%
“…Based on light irradiation from the ultraviolet, visible, and near-infrared spectrums, optical imaging techniques have high detection sensitivity but are limited by quenching and the photo-bleaching effect. Magnetic resonant imaging (MRI) is a radiation-free and non-invasive technique based on magnetic contrast agents such as Gadolinium (III), superparamagnetic iron oxide nanoparticles (SPIO), or perfluorocarbons (PFCs), and is characterized by high spatial resolution but with very low sensitivity 185 , 186 , 187 , 188 . Ionizing radiation such as positron emission tomography (PET) and single-photon emission computed tomography (SPECT) are based on the use of high-energy elements (radioisotopes) characterized by high-detection sensitivity (from nanomolar to picomolar) but with low spatial resolution 189 , 190 .…”
Section: Macrophage As Theranostic Toolsmentioning
confidence: 99%
“…19 F has a high relative sensitivity comparable to 1 H (83% of 1 H), and the 19 F signal can be more directly related to the presence of the label, compared to the T2* approaches described above with SPIOs. This quantifiable signal obtained from 19 F-based contrast agents is highly specific due to the lack of endogenous 19 F in biological tissues and provides positive rather than negative contrast which facilitates detection [56]. Perfluorocarbons (PFC) have been used for 19 F-MRI tracking of immune cells both clinically and preclinically.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…PFCs can be emulsified into lipid nanoemulsions or incorporated into the synthetic amino acid poly(lactide-co-glycolide) or PLGA to improve biocompatibility for imaging applications [57,58]. Commonly used PFCs include perfluoro-15-crown-5 ether and perfluoropolyether [56]. Perfluoro-15-crown-5 ether has been used for imaging neutrophils and monocyte infiltration in a preclinical model of lipopolysaccharide (LPS) bacterial endotoxininduced inflammation [40].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…In the past, it has been shown that intravenous injection of PFCs results in cellular uptake by circulating monocytes and macrophages that leads to an accumulation of 19 F atoms at sites of inflammation 19 . This technology has been successfully used for imaging a variety of different inflammatory diseases like myocardial infarction, myocarditis, transplant rejection and pneumonia 21 . To further enhance the specificity of PFCs, and to expand the repertoire of target cells and structures we have recently established a platform to functionalize PFCs with specific ligands 30 , 32 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Perfluorocarbons are not soluble in water and instead are emulsified with lipids to form stable perfluorocarbon nanoemulsions (PFCs) with droplet sizes of 100–200 nm. Intravenous administration of PFCs leads to strong phagocytic uptake by monocytes and macrophages that accumulate at inflammatory lesions which has been successfully used for imaging inflammation in diseases like myocardial infarction, myocarditis, transplant rejection or pneumonia by combined 1 H/ 19 F MRI 20 , 21 . Interestingly, 19 F MRI has also been used in theranostic applications since combining targeted drug delivery with imaging offers the unique possibility to determine if and how much of the therapeutic agent reaches the desired target tissue and how this impacts disease development 22 .…”
Section: Introductionmentioning
confidence: 99%